Review and analysis of 2023 Clinical Guidelines for Lipid Metabolism Disorders - I. V. Sergienko; M. V. Ezhov (Российский кардиологический журнал)
The novelty of the 2023 National Guidelines for Lipid Metabolism Disorders is presented regarding the categorization of cardiovascular risk, target and optimal levels of blood lipids, diagnosis and therapeutic approaches to the treatment of dyslipidemia.